The Evolution of Individualistic Norms - Don Ross (Baltic International Yearbook of Cognition, Logic and Communication, 2012)
It is generally recognized that descriptive and normative individualism are logically independent theses. This paper defends the stronger view that recognition of the falsehood of descriptive individualism is crucial to understanding the evolutionary and developmental basis of normative individualism. The argument given for this is not analytic; rather, it is based on empirical generalizations about the evolution of markets with specialized labor, about the nature of information processing in large markets, and about the socialization of human children.